Dibs on that Sexy Piece of Ass: Hegemonic Masculinity on TFM Girls Instagram Account. (February 2018) - Rodriguez, Nathian Shae; Hernandez, Terri
The study examines how the TFM Girls Instagram account, along with its followers, shapes and maintains dominant discourses of masculinity. Mixed-method analyses revealed that women were depicted more in bikinis, posed in overtly sexually suggestive poses, excluded the women's eyes and faces, and included predominately White, fit, big-breasted women. There was a positive correlation between the number of likes/comments with breast size. There were also instances of misogyny and objectification manifested in the men's comments attached to the photographs. The results highlight Instagram as a digital extension of fraternal social spaces. TFM Girls reinforces hegemonic masculinity on a macro-level by allowing virtual linkages among fraternity members across the United States and by fostering a national online frat house ripe with misogyny and objectification.